Functional Analysis of GLRX5 Mutants Reveals Distinct Functionalities of GLRX5 Protein. Issue 1 (January 2016) - Liu, Gang; Wang, Yongwei; Anderson, Gregory J.; Camaschella, Clara; Chang, Yanzhong; Nie, Guangjun
ABSTRACT: Glutaredoxin 5 (GLRX5) is a 156 amino acid mitochondrial protein that plays an essential role in mitochondrial iron‐sulfur cluster transfer. Mutations in this protein were reported to result in sideroblastic anemia and variant nonketotic hyperglycinemia in human. Recently, we have characterized a Chinese congenital sideroblastic anemia patient who has two compound heterozygous missense mutations (c. 301 A>C and c. 443 T>C) in his GLRX5 gene. Herein, we developed a GLRX5 knockout K562 cell line and studied the biochemical functions of the identified pathogenic mutations and other conserved amino acids with predicted essential functions. We observed that the K101Q mutation (due to c. 301 A>C mutation) may prevent the binding of [Fe‐S] to GLRX5 protein, while L148S (due to c. 443 T>C mutation) may interfere with [Fe‐S] transfer from GLRX5 to iron regulatory protein 1 (IRP1), mitochondrial aconitase (m‐aconitase) and ferrochelatase. We also demonstrated that L148S is functionally complementary to the K51del mutant with respect to Fe/S‐ferrochelatase, Fe/S‐IRP1, Fe/S‐succinate dehydrogenase, and Fe/S‐m‐aconitase biosynthesis and lipoylation of pyruvate dehydrogenase complex and α‐ketoglutarate dehydrogenase complex. Furthermore, we demonstrated that the mutations of highly conserved amino acid residues in GLRX5 protein can have different effects on downstream Fe/S proteins. Collectively, our current work demonstrates that GLRX5 protein is multifunctional in [Fe‐S] protein synthesis and maturation and defects of the different amino acids of the protein will lead to distinct effects on downstream Fe/S biosynthesis. J. Cell. Biochem. 117: 207–217, 2016. © 2015 Wiley Periodicals, Inc.